2021
DOI: 10.1088/1361-6560/abf2f8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of automatic detection of small hepatocellular carcinoma (≤2 cm) in cirrhotic liver based on pattern matching and deep learning

Abstract: Background and objective. Early detection of hepatocellular carcinoma (HCC) is crucial for clinical management. Current studies have reported large HCC detections using automatic algorithms, but there is a lack of research on automatic detection of small HCCs (sHCCs). This study is to investigate the feasibility of automatic detection of sHCC (≤2 cm) based on pattern matching and deep learning (PM-DL) model. Materials and methods. A retrospective study included 5376 image sets from 56 cirrhosis patients (28 sH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…One study developed a deep-learning algorithm for detecting HCCs on HBP images, which showed comparable performance to less-experienced radiologists on external datasets (sensitivity and specificity, 87% vs. 86% and 93% vs. 92%, respectively) [ 127 ]. Other studies also showed relatively good performance of deep-learning algorithms for detecting HCCs on CT (sensitivity, 92.0% and false-positive rate, 13.7%) or MRI (sensitivity, 89.7% and positive predictive value, 85.0% for lesions ≤2 cm) [ 128 , 129 ]. Regarding LI-RADS, one study reported that deep learning methods on MRI can distinguish between LR-3 and LR-4 or LR-5 lesions with an accuracy of 90% in the test set [ 130 ].…”
Section: Future Aspects For Hcc Surveillance and Diagnosismentioning
confidence: 99%
“…One study developed a deep-learning algorithm for detecting HCCs on HBP images, which showed comparable performance to less-experienced radiologists on external datasets (sensitivity and specificity, 87% vs. 86% and 93% vs. 92%, respectively) [ 127 ]. Other studies also showed relatively good performance of deep-learning algorithms for detecting HCCs on CT (sensitivity, 92.0% and false-positive rate, 13.7%) or MRI (sensitivity, 89.7% and positive predictive value, 85.0% for lesions ≤2 cm) [ 128 , 129 ]. Regarding LI-RADS, one study reported that deep learning methods on MRI can distinguish between LR-3 and LR-4 or LR-5 lesions with an accuracy of 90% in the test set [ 130 ].…”
Section: Future Aspects For Hcc Surveillance and Diagnosismentioning
confidence: 99%
“…Zheng et al (2022) performed automatic liver tumor segmentation based on threedimensional convolution and convolutional long short-term memory-based model. Additionally, diffusionweighted imaging and multi-phasic DCE were used to develop a workflow based on pattern recognition and neural network by Zheng et al (2021). The late hepatocellular phase of DCE MRI was also used for deep learningbased liver tumor segmentation by Hänsch et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhu et al(56) studied the application value of histogram features on IVIM-DWI in the differential diagnosis of HCC. They found that the histogram parameters of IVIM-DWI could distinguish hepatic hemangiomas, hepatic cysts, and HCC and that the volume of the pseudodiffusion coefficient and perfusion fraction had better diagnostic value than other histogram parameters(56).In recent years, DL technology has been developed and has achieved excellent performance in the classification of hepatic lesions(65)(66)(67)(68)(69)(70)(71).Hamm CA et al (65) developed a proof-ofconcept convolutional neural network (CNN)-based DL system and classified 494 hepatic lesions from six categories on MRI.…”
mentioning
confidence: 99%